Particulate organic carbon is a sensitive indicator of soil degradation related to overgrazing in Patagonian wet and mesic meadows - Enriquez, Andrea Soledad; Cremona, Maria Victoria (Springer, 2019)
Patagonian meadows are key for the development and sustainability of rural environments. However, they have been degraded due to a combination of weather conditions and overgrazing. Total soil organic carbon (TOC) has been found as a moderate indicator of meadow soil degradation by long-term heavy grazing. The aim of this study was to evaluate the particulate organic carbon (POC) (a more labile fraction of the soil organic matter) as an ecological indicator for assessing soil changes in natural Patagonian meadows, related to different longterm grazing managements. We worked in three locations along a precipitation gradient in Northern Patagonia. Each location has wet and mesic meadows with good and poor grassland condition, attributed to two long-term grazing pressures (light and heavy). We sampled soil throughout the plant-growing season following the natural soil moisture fluctuations, and quantified the POC content, the POC:TOC ratio, and the F[53 proportion. Along the different sampling dates, significant differences between good versus poor grassland condition were found in many cases in POC, a few in POC:TOC ratio, and none in F[53 proportion. The POC varies over time, in association with changes in the soil moisture (adjusted R2 vary between 0.76 and 0.99); therefore, the sampling date must be standardized (we recommend dry periods). The POC appears to be a sensitive indicator when assessing the effect of different soil management practices on soil quality, an important step for meadow conservation, restoration and sustainable use, but further research is needed to validate this exploratory study.